81.9k views
4 votes
Gven the following table, find the rate of change between f(-4) and f(0) x -4 -2 0 2 4 f(x) -2 -1 0 1 2A. -2 B. 2 C. -1/2 D. 1/2

User Dyomas
by
5.5k points

1 Answer

6 votes

Gven the following table, find the rate of change between f(-4) and f(0)



x -4 -2 0 2 4

f(x) -2 -1 0 1 2



A. -2

B. 2

C. -1/2

D. 1/2 ​

we know that

the rate of change is equal to

(f(b)-f(a))/(b-a)

f(b)=f(0)

f(a)=f(-4)

b=0

a=-4

(f(0)-f(-4))/(0+4)

we have that

f(0)=0

f(-4)=-2

substitute

(0+2)/4

2/4

1/2

therefore

the answer is the option D

User Manu Mohan
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.